Exploiting acquired vulnerability to develop novel treatments for cholangiocarcinoma - Sirayot Areewong; Orawan Suppramote; Sunisa Prasopporn; Siwanon Jirawatnotai (Cancer Cell International)
Abstract Cholangiocarcinoma (CCA) presents a formidable therapeutic challenge due to its extensive heterogeneity and plasticity, which inevitably lead to acquired resistance to current treatments. However, recent evidence suggests that acquired drug resistance is associated with a fitness cost resulting from the myriad of acquired alterations under the selective pressure of the primary treatment. Consequently, CCA patients with acquired resistance are more susceptible to alternative therapies that are ineffective as monotherapies. This phenomenon, termed “acquired vulnerability,” has garnered significant interest in drug development, as the acquired alterations could potentially be exploited therapeutically. This review elucidates the modes of acquired vulnerability, methods for identifying and exploiting acquired vulnerabilities in cancer (particularly in CCA), and strategies to enhance the clinical efficacy of drug combinations by leveraging the principle of acquired vulnerability. Identifying acquired vulnerabilities may pave the way for novel drug combinations to effectively treat highly heterogeneous and adaptable malignancies such as CCA.